Teacher Perfectionism and Iranian English Language Learnersâ€™ Motivation and Achievement - Rezvani, Reza; Pakdaman, Safiyeh; Bigdeli, Rouhollah Askari (Widya Mandala Catholic University Surabaya, 2015)
Educational psychology has recently reflected a policy shift from focusing on â€œwhat goes wrongâ€ in schools, including psychological, physical, and educational disabilities, to recognizing and promoting strengths and positive aspects of students and their environments. Within this scope, some lines of research have examined the extent to which setting personal high standards influences such positive outcomes as educational achievement and high level of motivation. The present study was motivated by the concern that Iranian English language teachers' setting high standards, i.e. perfectionism, may predict English language learnersâ€™ motivation and language achievement. Through cluster random sampling, a total of 30 English language teachers with more than one year of experience and 300 elementary English language learners were selected from English Language Institutes in Fars province, Iran. Frost Multidimensional Perfectionism scale and Motivations Underlying English Language Learning questionnaire were used to measure teachers' perfectionism and learnersâ€™ language learning motivation, respectively. The learners' final scores in the English courses were collected as a measure of their language learning achievement. The result of simple regression analysis revealed that the teachers' perfectionism did not predict English language learnersâ€™ motivation and language achievement. In other words, Iranian English language teachers' perfectionism did not account for any variance in these two variables of interest. Keywords: Perfectionism, Motivation, Language Learning Achievement